Influence Analysis of Magnetic Track Beam Irregularity on the Suspended State - LI Ping; HU Wenwen (机车电传动)
Through the establishment of a single magnet-suspension system-track beam interaction model, characteristic requirements of track beam was described, and state change of a single magnet in suspension was studied from track beam long-wave irregularity, shortwave irregularity, track beam stiffness and speed of vehicles. The results showed that: single magnet levitation gap change increased as the speed increasing; short-wave irregularity impacting on the vehicle was severer than the long-wave irregularity impacting, and shortwave irregularity had a greater impact on a single magnetic levitation gap and vibration acceleration; track beam stiffness of the rail beam influenced the deflection changes the most significantly, but had little effect on the levitation gap and single magnet vibration acceleration.